Vivere insieme. Intimità e quotidianità nelle convivenze interculturali tra rifugiati e italiani a Parma - Giuffrè, Martina; Marchetti, Chiara (Antropologia Pubblica, 2024)
Sharing everyday life contexts between Italian and foreigners represents an important opportunity to build significant new practices of conviviality in the urban space. In particular, while opportunities for meeting and exchange are multiplying in the cities, the most intimate experiences of living together between natives and foreigners, beyond what concerns sentimental and family ties, are not so widespread yet, especially when they concern - for the foreign component- refugees and other forced migrants. Specifically, in this essay we focus on the cohabitation that took place in Parma on the initiative of CIAC association. The two projects provide, on the one hand, the hospitality of refugees in local family’s homes and, on the other hand, the co-housing of young Italians and refugees. During the two years research we used the peer research methodology that involves the protagonists of the two mentioned projects both as co-researchers and interviewees. This approach offers the opportunity to activate reflexivity processes on the forms of reception and living, and to critically rethink concepts at the centre of socio-anthropological debate such as those of intimacy, family, home, intercultural relations, through a privileged observation point starting from the intimate dimension of daily practices (as for example eating and cooking together, sharing domestic space and their care) and projecting outwards into the spaces of the city and beyond.